2017
DOI: 10.1371/journal.pntd.0005640
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale variation in microclimate across an urban landscape shapes variation in mosquito population dynamics and the potential of Aedes albopictus to transmit arboviral disease

Abstract: Most statistical and mechanistic models used to predict mosquito-borne disease transmission incorporate climate drivers of disease transmission by utilizing environmental data collected at geographic scales that are potentially coarser than what mosquito populations may actually experience. Temperature and relative humidity can vary greatly between indoor and outdoor environments, and can be influenced strongly by variation in landscape features. In the Aedes albopictus system, we conducted a proof-of-concept … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(142 citation statements)
references
References 120 publications
7
114
1
1
Order By: Relevance
“…Carrington et al, in a study conducted in northwest Thailand have found that large diurnal temperature range (DTR) adversely affects mosquito biology by extending immature development phase, lowered larval survival and reduced female reproductive capacity (Carrington et al, 2013a). Our findings of mosquito abundance and DTR reinforce these findings along with those from a diversity of laboratory studies demonstrating the effects of DTR (Lambrechts et al, 2011;Carrington et al, 2013b;Carrington et al, 2013c;Liu-Helmersson et al, 2014;Murdock et al, 2017) on a variety of mosquito life history traits like survival, fecundity, larval development, biting rates, vector competence, and viral transmissions.…”
Section: Discussionsupporting
confidence: 86%
“…Carrington et al, in a study conducted in northwest Thailand have found that large diurnal temperature range (DTR) adversely affects mosquito biology by extending immature development phase, lowered larval survival and reduced female reproductive capacity (Carrington et al, 2013a). Our findings of mosquito abundance and DTR reinforce these findings along with those from a diversity of laboratory studies demonstrating the effects of DTR (Lambrechts et al, 2011;Carrington et al, 2013b;Carrington et al, 2013c;Liu-Helmersson et al, 2014;Murdock et al, 2017) on a variety of mosquito life history traits like survival, fecundity, larval development, biting rates, vector competence, and viral transmissions.…”
Section: Discussionsupporting
confidence: 86%
“…(8) Microclimates and habitats vary in temperature. While studies often focus on constant or mean temperatures, in the field vectors can preferentially occupy habitats with favourable microclimates (Paaijmans et al 2010b;Paaijmans & Thomas 2011b;Murdock et al 2017). How much do microhabitat availability and preferences moderate the effects of average temperatures on transmission?…”
Section: Foundational Concepts In Thermal Biologymentioning
confidence: 99%
“…Collect mosquitoes in their preferred resting and breeding habitats in the field. Experimentally measure traits in different microclimates in the field (Murdock et al 2017). Adapt mechanistic models to incorporate temperatures from relevant microclimates, rather than averages over larger spatial scales.…”
Section: Foundational Concepts In Thermal Biologymentioning
confidence: 99%
“…It is possible that other microclimate factors may influence mosquito larval development. For example, relative humidity is expected to be greater in logged forest than in oil palm (Hardwick et al 2015), which could decrease the surface tension of water in the experimental pots (Pérez-Díaz et al 2012) and thereby impact mosquito pupation success (Murdock et al 2017). An alternative explanation for the absence of a land-use effect on development during the ENSO drought is that the elevated temperatures in the oil palm plantation were high enough to cause stress and reduce the fitness of developing mosquitoes (Feder and Hofmann 1999).…”
Section: Land-use and Enso Synergistically Affect Mosquito Developmentmentioning
confidence: 99%